Moral Emotions and Social Economic Games in Paranoia - Savulich, George; Jeanes, Hannah; Rossides, Nicole; Kaur, Sahaj; Zacharia, Alice; Robbins, Trevor W.; Sahakian, Barbara J. (Frontiers in Psychiatry, 2018)
Impaired social cognitive processes are putative psychological mechanisms implicated in the formation and maintenance of paranoid beliefs. Paranoia denotes unfounded fears about the hostile intentions of others and is prevalent in a significant proportion of the general population. We investigated social cognition in healthy participants selectively recruited to have a broad occurrence of paranoid thinking (n = 89). Participants completed a novel computerised task of moral emotions and two social economic exchange games (Prisoner’s Dilemma, Ultimatum Game) from the EMOTICOM neuropsychological test battery. Regression analyses revealed that delusional ideation predicted shameful feelings when the victim of deliberate harm by another person. Cooperative behaviour on the Prisoner’s Dilemma was greatest when the participant and opponent contributed equally to joint earnings. Participants demonstrated significantly more punishment behaviour when contributions were unequal and stole more from the opponent using a suspicious strategy of gameplay. In addition, paranoid thinking was positively associated with more stealing from the cooperative opponent. On the Ultimatum Game, participants accepted significantly more unequal offers when the opponent contributed more and sensitivity to fairness was greatest when the participant contributed more. These data demonstrate that delusional ideation predicts a maladaptive emotional response to interpersonal harm and that paranoid thinking may lead to reduced cooperation toward mutual reward. The effects of paranoia on moral emotions and pro-social behaviour at more severe levels of persecutory thinking warrant further investigation.